العوامل المؤسساتية المفسرة لظاهرة الاقتصاد غير الرسمي في الجزائر - دراسة تحليلية بالاعتماد على تقرير ممارسة أنشطة الأعمال لسنة 2018 – - بيلامي, مريم (جامعة الوادي - University of Eloued, 2020)
ملخص: الهدف من هذه الدراسة هو تحليل العوامل المؤسساتية المفسرة لظاهرة الاقتصاد غير الرسمي في الجزائر. و أبرز ما توصلت اليه هذه الدراسة هو أن حجم الاقتصاد غير الرسمي في الجزائر عرف نموا مستمرا في السنوات الأخيرة و هذا ما سمح بتوفير فرص عمل في القطاع غير الرسمي. ففي الواقع، تعتبر هذه العوامل المؤسساتية و المتمثلة في: صعوبة الحصول على الائتمان، ثقل الأعباء الضريبية ، ضعف حماية المستثمرين ، تعقد الإجراءات الإدارية التي سمحت بانتشار البيروقراطية ، صعوبة إنشاء مؤسسة و استخراج تراخيص البناء ، الفساد الإداري ، انعدام الشفافية ، صعوبة إجراءات تسجيل و نقل الملكية و نقص ثقة المتعاملين في الإطار الرسمي للدولة من العوائق التي يواجهها الأفراد عند ممارسة أنشطتهم بصفة عادية مما يمنعهم من البقاء في القطاع الرسمي و يشجعهم لممارسة أنشطة غير رسمية. Abstract: The objective of this study is to analyze the institutional factors explaining the phenomenon of the informal economy in Algeria. The main findings of this study are that the size of the informal economy in Algeria has grown steadily in recent years, which has allowed jobs to be provided in the informal sector. In fact, these institutional factors: the difficulty of obtaining credit, the weight of tax burdens, the weak protection of investors, the complexity of administrative procedures that allowed the spread of bureaucracy, the difficulty of establishing an institution and the extraction of building permits, administrative corruption, lack of transparency, The difficulty of registering and transferring property and the lack of confidence of dealers in the official state framework of the obstacles faced by individuals in the normal conduct of their activities, which prevents them from remaining in the formal sector and encourages them to engage in informal activities. Keywords: Informal economy, informal sector, informal employment, institutional factors. Jel Classification Codes : E26-O17
The institutional factors explaining the phenomenon of the informal economy in Algeria - An analytical study based on the Doing Business report of 2018 –
Keywords: الاقتصاد غير الرسمي- ; القطاع غير الرسمي- ; التشغيل غير الرسمي- ; الع ; امل المؤسساتية